Sustainability and law : general and specific aspects - Mauerhofer, Volker; Rupo, Daniela; Tarquinio, Lara (Cham, Switzerland : Springer, 2020)
The book discusses sustainability and law in a multifaceted way. Together, sustainability and law are an emerging challenge for research and science. This volume contributes through an interdisciplinary concept to its further exploration. The contributions explore this exciting domain with innovative ideas and replicable approaches. It combines a variety of authors, from both the public and the private sectors, and thereby guarantees a broad view that enshrines the more theoretical arguments from the academic side as well as stronger practical applicable perspectives. The book provides space for thoughtful expansions of established theories as well as the hopeful emergence of innovative ideas. Moreover, the combination of three to five contributions into the eleven parts respectively aims toward a compression of like minded thoughts. This should lead to an intensification of exchange of viewpoints from different angles on a similar theme. Readers therefore also have the opportunity to concentrate on single chapters, but receive comprised knowledge and a variety of thoughts for new ideas on a particular theme
Introduction / Danile Rupo, Lara Tarquinio, and Volker Mauerhofer -- Sustainable Development Law in (Only) One World: Challenges and Perspectives for Governance and Governments / Volker Mauerhofer -- Designing Law for Sustainability / Massimiliano Montini -- The Laws of Sustainable Development / Geert van Calster -- Reducing the European Union's Environmental Footprint Through "Territorial Extension" / Joanne Scott -- Resilience : Is Sustainability Dead? / Trevor Daya-Winterbottom -- What Does the Rebound Effect Tell Us? Reflection on Its Sources and Its Implication for the Sustainability Debate / Joelle Saey-Volckrick -- Regulating our Consumer Culture: What Role Can the Law Play in Addressing Excessive Consumption? / Melissa Gorrie -- Biodiversity, Climate Change and Finnish Forest Regulation / Minna Pappila -- "The Chemicals Between Us": The Use and Discharge of Chemicals in the Life Cycle of a Pair of Jeans - From Legal Theory to Practice / Martine Bosman, Tineke Lambooy, Elif Oral, and Bart Jansen --| Fiscal Policy for Sustainable Development: The Italian Way to Promote Innovative Entrepreneurship According to European Union Rules / Patrizia Accordino -- Planned Obsolescence and Criminal Law: A Problematic Relationship? / Emanuele La Rosa -- Political Corporate Social Responsibility and the Role of Companies. Evidence from Novo Nordisk / Stefania Carolina Posadas, Lara Tarquino, and Michele A. Rea -- Italy Towards Mandatory Sustainability Reporting : Voluntary Corporate Social Responsibility Disclosure of Italian Companies and Legislative Decree 254/2016 Statements: A Quantitative Analysis of the Last 10 Years / Federica Balluchi, Katia Furlotti, and Riccardo Torelli -- Non-financial Performance Indicators: The Power of Measures to Operationalize the Law / Domenico Raucci, Lara Tarquino, Daniela Rupo, and Salvatore Loprevite -- Collaborative Regulation: Preventing Regulatory Capture in Multi-stakeholder Processes for Developing Norms for Sustainability Conduct / Karin Buhmann -- Right to Development and Right to Environment: Sustainable Development Perspectives / Ivana Savic -- Peace as a Right of Humanity / Iryna Ivankiv -- NGOs as Loudspeakers : Potential Role of NGOs in Bridging the North-South Gap in International Environmental and Sustainable Development Law Making Process / Kokila Konasinghe -- Claims in Environmental Civil Public Interest Litigation in China: Problems and Solutions / Xuemin Chen and Tianbao Qin -- Rules and Practices of International Law on Benefit-Sharing for Sustainable Development / Jorge Cabrera Medaglia, Frederic Perron-Welch -- Sustainable Use of Indigenous Ecological Knowledge: A Case Study for Implementing the Nagoya Protocol / Natalie P. Stoianoff -- Jatropha Cultivation in South India - Policy Implications / Lakshmi Gopakumar -- Invasive Alien Species - The Eradication or Use of Invasive Alien Species Under EU Law / Felix Frommelt -- The Limited Contribution of Environmental Law to the Sustainable Management of Marine Resources in Brazil: The Need for an Integrated Approach / Carina Costa de Oliveira, Gabriela G.B. Lima Moraes, and Priscila Pereira de Andrade -- International Environmental Law and Law of the Sea: Analysis of Legal and Political Aspects of Institution Interaction / Ekaterina Vasilenko and Ekaterina Bliznetskaya -- From Global to Local: A Multilevel Approach to the Local Implementation of Climate Policies in Japan / Hitomi Roppongi -- Integrating Sustainability in Governance and Legal Framework for a Sustainable Builtscape in Kenya: Towards a Global Approach / Ruth Onkangi and Yvonne Getugi -- Towards a Low/Zero Carbon Society for the Asia-Pacific Region: Policy and Legal Development for Carbon Capture and Storage (CCS) in Japan / K. Yanagi and A. Nakamura -- Framing Ecosystem Services for Sustainability? / Alexandra Langlais -- Mainstreaming Ecosystem Services as Public Policy in South East Asia, from Theory to Practice / Ho Huu Loc, Kim N. Irvine, Asan Suwanarit, Pakorn Vallikul, Fa Likitswat, Alisa Sahavacharin, Chansopheaktra Sovann, and Le Song Ha -- Payment for Ecosystem Services in the Congo Basin: Filling the Gap Between Law and Sustainability for an Optimal Preservation of Ecosystem Services / Blaise-Pascal Ntirumenyerwa Mihigo and An Cliquet -- Municipalities, Social Innovations, and the Co-development of Localized Food Rights / Paula Fernandez-Wulff -- Water-Energy-Food Nexus and Groundwater: Can the Nexus Support the Sustainable Management of Transboundary Aquifers? / Imad Antoine Ibrahim -- Establishing Urban Gardens on Vacant Land While Considering International Good Practices: A Legal Case Study from Portugal / Alexandra Ribeiro, Raquel Carvalho, and Livia Madureira -- Summary and Conclusions / Volker Mauerhofer, Daniela Rupo, and Lara Tarquino.
Includes bibliographical references
Keywords: Sustainable development -- Law and legislation; Environmental law; Sustainable development -- Government policy